Função afim y = ax + b: a articulação entre os registros gráfico e algébrico com o auxílio de um software educativo - Santos, Edivaldo Pinto dos (2002)
The aim of this work is to study the acquisition of knowledge related to the coefficients of the equation y = ax + b by means of articulating the graphical and algebraic registers associated with affine functions with the help of a software environment especially constructed for this purpose. To this end, a didactic sequence was designed based on some principles of computer education and on notions from the theory of Raymond Duval (1999), who considers that a global interpretation procedure is important for graphical registers as well as taking into account the discrimination of relevant visual and the perception of variations corresponding to written algebra. A group of 5 pairs of students (aged 16-17 years) from a private school in São Paulo worked through the sequence. The results indicated that an evolution occurred in relation to the construction of meanings of the coefficients of the algebraic representations of affine functions associated with their graphical representations, that is, the corresponding line. The investigation shows that the software environment used in the study enabled new ways of working with students, assessing their progress and developing teaching and learning processes related to affine functions and particularly of conversion from the graphical register to the algebraic